(untitled) (Vietnam Journal of Community Medicine, 2025)
ABSTRACT Objective: To evaluate the relationship between depth of anesthesia (BIS) and Propofol dose during the cardiopulmonary bypass (CPB) phase in patients undergoing open-heart surgery, to determine the role of BIS in individualizing anesthetic dosing. Objects and methods: Observational and descriptive study and analysis on patients with indications for cardiovascular surgery using extracorporeal circulation at the Center for Anesthesia and Surgical Resuscitation, Viet Duc University Hospital from November 2024 to July 2025. Results: Within a sample of 51 patients, the average BIS value during CPB was 44.14 ± 1.89, and the mean Propofol dosage was 2.91 ± 0.14 mg/kg/hour. BIS values showed a moderate negative correlation with Propofol dosage (r = -0.40; p = 0.003); and each increase of 1 mg/kg/hour in Propofol dosage led to an average 5.26 points decrease of 5.26 BIS. Conclusion: BIS values are moderately and inversely correlated with Propofol dosage during cardiopulmonary bypass.